Hierarchical Ceramic Coating Reduces Adherence of Cells, Blood, Bacteria, and Tissue on Titanium Microsurgical Instruments - Jaurich, Henriette; Becerikli, Mustafa; Zerrer, Jörg; Wallner, Christoph; Wagner, Johannes M.; Dadras, Mehran; Jettkant, Birger; Schildhauer, Thomas A.; Lehnhardt, Marcus; Jung, Ole; Behr, Björn (Journal of Reconstructive Microsurgery, 2021)
Background Progress in the field of microsurgery allows more detailed reconstructions of the smallest tissue structures. The applied instruments are left with biological residues after coming into contact with body fluids or tissue, leading to compromised surgical precision. Designing of residue-free innovative instruments would reduce the necessity of subsidiary practices and would improve the surgical precision.Methods We designed a ceramic coating (Lotus ceramic coating system 26—LCC-26) that exhibits self-cleaning surface properties on coated titanium specimens. A titanium surface was modified by blasting technology and electropolishing, followed by applying a high-performance ceramic and sol-gel finish layer. The physical surface characterization was performed by scanning electron microscopy and measuring the contact angle. The cell-repellent properties and cytotoxicity were investigated using live-dead staining, BrdU, and lactate dehydrogenase assay. Furthermore, bacterial and fluid-adhesion tests were performed. Finally, blood compatibility was analyzed according to DIN ISO 10993.Results The composite system LCC-26 increased the hydrophobic character of the titanium surface (the water contact angle of 74.9 degrees was compared with 62.7 degrees of the uncoated native titanium; p < 0.01) and led to the fluid and cell-repellent properties shown by the reduction in fibroblast adherence by ∼50.7% (p < 0.05), the reduction in Staphylococcus aureus pathogen colonization by 74.1% (p < 0.001), and the decrease in erythrocyte adherence by 62.9% (p < 0.01). Furthermore, the LCC-26 coated titanium microforceps dipped in human whole blood exhibited blood-repellent character (reduction in blood adherence by 46.1%; p < 0.05). Additionally, cyto- and hemocompatibility was guaranteed in direct and indirect tests.Conclusion Titanium surface modification on surgical instruments exhibits cell, bacteria, and blood-repellent properties with a full guarantee of cyto- and hemocompatibility. Thus, innovatively coated instruments could contribute to increased precision during microsurgical interventions and optimized medical operation routines in the future.
Keywords: surface modification; titanium; self-cleaning instrument; cyto- and hemocompatibility